RANCANG BANGUN SISTEM INFORMASI PERPUSTAKAAN BERBASIS WEB (STUDI KASUS: UNIVERSITAS KUNINGAN) - Aji Permana (Cloud Information, 2018)
Design of a web based Library Information (A Case Study at Kuningan University) is a means to manage and obtain book library data that exist in the University of Kuningan. The management of this application includes book collection with book code, book lending, book returns, borrowing fines and so on which are integrated between the University library data and the available library data in the faculty. This library system will be integrated with the academic system for verification of certificate submission data in which the students must submit the final project result, paper or thesis along with the statement stating that the students do not have a loan or arrears in the library. The results obtained in this library information system is in the form of reports of data visits, registration, borrowing, returns and penalties with adjustable output per Faculty, department, academic year and overall.Keywords: Library Information System, University of Kuningan, Online Library, WEB-based Library